Study of optoelectronic energy bands and molecular energy levels of tris (8-hydroxyquinolinate) gallium and aluminum organometallic materials from their spectroscopic and electrochemical analysis - Muhammad, F.F.; Hapip, A.I.A.; Sulaiman, Khaulah (Elsevier, 2010)
For the purpose of investigating electro-molecular absorption bands, energy gaps, E(g) and molecular energy levels (ionization potential, IP and electron affinity, EA) of tris (8-hydroxyquinolinate) gallium and aluminum, spectral analysis in conjunction with electrochemical measurements was carried out. UV-Vis-NIR and FTIR spectroscopic measurements were used to assign the electronic and molecular absorption bands in both of the materials. The XRD and scanning electronic microscopy (SEM) technique showed the amorphous nature. From the recorded data of cyclic voltammetry (CV) and materials absorption coefficient, HOMO, LUMO energy levels and energy gaps for Gaq3 and Alq3 were calculated. A bit smaller value of energy gap for Gaq3 (2.80 eV) compared to that of Alq3 (2.86 eV) has been ascribed to the differences in electronic configuration and coordinated bond lengths related to the central metal atom with respect to the quinolinate ligands. A higher value of HOMO energy level for the Alq3 (IP = 6.3 eV) revealed the need of higher potentials to oxidize its molecules comparing to that of Gaq3 (IP = 5.8 eV). It was observed that cationic metals have a direct effect on the physical and chemical behaviors of such organometallic materials that can be exploited to be used in tuning their properties to match the desired application in OSC and/or OLED technologies. (C) 2010 Elsevier B.V. All rights reserved.